Attitudes and Opinions of Classical Philology Students in Greece Regarding the Teaching Quality of Their Studies - Fykaris, Ioannis (International Research in Education, 2024)
This research emerged from a contemplation regarding the quality of teaching and the content of studies provided to Classical Philology students, aiming for the optimal enhancement of their education. A literature review revealed the innovative nature of this research, as no similar studies were identified in both the Greek and international contexts. Consequently, it can be argued that this research could serve as a reference point for further similar investigations.